KAPABILITAS PEMERINTAH DESA DALAM MENERAPKAN KONSEP DESA CERDAS MELALUI PELAYANAN ADMINISTRASI DESA BERBASIS DIGITAL DI DESA PANDAU JAYA DAN DESA SIBUAK KABUPATEN KAMPAR TAHUN 2021-2023 - Robani, Muhammad Agung; ', Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
A Smart Village is a village that is able to improve the welfare and quality of life of the community through the use of technology in various aspects of village development. Pandau Jaya Village is included in the Smart Village Locus for Kampar Regency in 2021 and is participating in the Smart Village activity program, the same as Sibuak Village. However, Pandau Jaya Village has not been able to implement the Smart Village concept through digital-based village administration services. This is different from Sibuak Village which has been able to implement the Smart Village concept through digital-based village administration services. The aim of this research is to determine the capability of the village government in Pandau Jaya Village and Sibuak Village in implementing the Smart Village concept through digital-based village administration services in 2021-2023. This research uses Kusumasari's capability theory, the resources and important factors that the government must have to create a well-capable organization, namely institutional, human, financial and technical resources. The approach used in this research is a qualitative approach. This type of research is descriptive. The location of this research is Pandau Jaya Village and Sibuak Village. The type of data in this research is divided into primary data with data collection techniques through interviews and secondary data in the form of supporting data related to the Smart Village program. The data collection techniques are through interviews and documentation. The data analysis technique used is a qualitative analysis technique. The results of this research are the capabilities of the Pandau Jaya and Sibuak Village Governments in implementing digital services in their villages. The capabilities of the Pandau Jaya Village Government and the Sibuak Village Government are not much different. The difference only lies in the technicalities in implementing the Smart Village concept. Keywords: Smart Village, Capabilities, Village Government